Anthocyanin content and storage stability of spray/freeze drying microencapsulated anthocyanins from berries : a review - Baeza, Rosa (2021)
Fil: Baeza, Rosa. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina